Collaborative Research for Excellence in Economics and Social Sciences Proceedings of the 2nd International Conference on Economics and Social Sciences - Mihaela Dima, Alina (Proceedings of the International Conference on Economics and Social Sciences, 2019)
Collaborative Research for Excellence in Economics and Social Sciences